On The Potential of Dynamic Nuclear Polarization Enhanced Diamonds in Solid‐State and Dissolution 13C NMR Spectroscopy. Issue 17 (15th July 2016) - Bretschneider, Christian O.; Akbey, Ümit; Aussenac, Fabien; Olsen, Greg L.; Feintuch, Akiva; Oschkinat, Hartmut; Frydman, Lucio
Abstract: Dynamic nuclear polarization (DNP) is a versatile option to improve the sensitivity of NMR and MRI. This versatility has elicited interest for overcoming potential limitations of these techniques, including the achievement of solid‐state polarization enhancement at ambient conditions, and the maximization of 13 C signal lifetimes for performing in vivo MRI scans. This study explores whether diamond's 13 C behavior in nano‐ and micro‐particles could be used to achieve these ends. The characteristics of diamond's DNP enhancement were analyzed for different magnetic fields, grain sizes, and sample environments ranging from cryogenic to ambient temperatures, in both solution and solid‐state experiments. It was found that 13 C NMR signals could be boosted by orders of magnitude in either low‐ or room‐temperature solid‐state DNP experiments by utilizing naturally occurring paramagnetic P1 substitutional nitrogen defects. We attribute this behavior to the unusually long electronic/nuclear spin‐lattice relaxation times characteristic of diamond, coupled with a time‐independent cross‐effect‐like polarization transfer mechanism facilitated by a matching of the nitrogen‐related hyperfine coupling and the 13 C Zeeman splitting. The efficiency of this solid‐state polarization process, however, is harder to exploit in dissolution DNP‐enhanced MRI contexts. The prospects for utilizing polarized diamond approaching nanoscale dimensions for both solid and solution applications are briefly discussed. Abstract : NMR hyperpolarization in diamonds : Nano‐ and micro‐sized diamonds can be hyperpolarized under cryogenic conditions by using nitrogen‐based defects, leading to long‐lived polarizations. However, their subsequent in vivo uses are challenged by solubility problems. At the same time, a highly efficient and weakly temperature‐dependent polarization process was found under magic angle spinning, and a spin‐physics model rationalizing this unusual behavior is given.